Uji Efektivitas Metarhizium Anisopliae sebagai Pengendali Larva Oryctes Rhinoceros di Perkebunan Kelapa Sawit - Toto Suryanto (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
Oryctes rhinoceros or horn beetle is one of the important pests of oil palm plants. These pests can cause very serious losses for palm oil production, so that proper control is needed so that pest attacks can be suppressed. This research aims to determine the concentration of Metarhizium anisopliae which is the most effective in controlling Oryctes rhinoceros larvae and understanding the difference between infected Oryctes rhinoceros and those not infected by Metarhizium anisopliae fungi. This research was conducted at Afdeling Charlie, Estate Berlian 1, PT Palmina Utama in Desa Cinta Puri Darussalam Village, Banjar District, Banjarmasin Regency, South Kalimantan Selatan in 3-30 Mei 2018. The experiment was used a descriptive method with 4 treatments: control (A0), 1 gr Metarhizium anisopliae / l water (A1), 2 gr Metarhizium anisopliae / l water (A2), 3 gr Metarhizium anisopliae / l water (A3). Each treatments were two replications so the total unit of experiments were 8 samples. The result showed that the highest mortality consentration of Oryctes rhinoceros larvae found in the treatment of 3 grams of Metarhizium anisopliae / l water (A3) of 47.50%. Oryctes rhinoceros larvae infected by Metarhizium anisopliae showed different conditions than the larvae of Oryctes rhinoceros which were not infected by Metarhizium anisopliae.